A modified electrode of a vanadium battery for inhibiting deposition of hydrogen on a negative side based on a flame spray pyrolysis technology, a preparation method and applications

CN122950503APending Publication Date: 2026-10-20INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611302396.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]针对现有钒电池负极析氢抑制技术中存在的抑制剂尺寸不可控、影响主反应活性等问题,本发明提供一种基于火焰喷雾热解技术的负极侧沉积析氢抑制团簇的钒电池电极改性方法

Benefits of technology

1、将火焰喷雾热解技术应用于钒电池负极析氢抑制团簇的沉积,实现了团簇的高效、可控、连续化制备,工艺简单、能耗低、易于规模化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention relates to a modified vanadium battery electrode based on flame spray pyrolysis technology, which deposits hydrogen evolution suppression clusters on the negative electrode side, along with its preparation method and application. The invention belongs to the field of vanadium battery electrode material modification technology. It utilizes flame spray pyrolysis technology to deposit sub-nanometer clusters with sizes ranging from 1 nm to 5 nm on the negative electrode side of a carbon-based electrode. By leveraging the size effect and electronic structure modulation of these clusters, it effectively suppresses the hydrogen evolution reaction while maintaining the inhibition of hydrogen evolution. 3+ / V 2+ The reaction exhibits high catalytic activity. The electrode surface loading of this invention is uniformly dispersed in clusters, enabling controllable preparation of sub-nanometer-scale clusters on a carbon substrate. This achieves efficient and continuous preparation of clusters with a simple process, low energy consumption, and ease of scalability. Simultaneously, it enables optimized control of hydrogen adsorption free energy, providing customized solutions for different application scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vanadium battery electrode material modification technology, specifically to a vanadium battery electrode based on flame spray pyrolysis technology with hydrogen evolution inhibition clusters deposited on the negative electrode side, its preparation method, and its application. By depositing hydrogen evolution inhibition clusters of a specific size on the negative electrode side, the invention achieves the suppression of hydrogen evolution side reactions and the maintenance of catalytic activity. Background Technology

[0002] Vanadium redox flow batteries (VRBs), as a large-scale energy storage technology, have broad application prospects in renewable energy grid integration and grid peak shaving due to their advantages such as high safety, long lifespan, and independent design of power and capacity. However, in actual operation, the hydrogen evolution reaction on the negative electrode side is one of the key issues affecting battery performance. The hydrogen evolution reaction refers to the side reaction during charging where hydrogen ions combine with electrons to generate hydrogen gas. In vanadium batteries, the Vevolution reaction occurs on the negative electrode side. 3+ / V 2+ The reduction reaction has a standard electrode potential of -0.26V vs. SHE, which is close to the hydrogen evolution potential. When there is local overpotential or the catalytic site is unfavorable for the reduction of vanadium ions, the hydrogen evolution reaction will occur preferentially, leading to a decrease in coulombic efficiency, electrolyte imbalance, and in severe cases, battery swelling and safety issues.

[0003] Existing methods for suppressing hydrogen evolution mainly include electrolyte additive modification and electrode surface coating. However, these methods often suffer from problems such as uneven inhibitor distribution, poor long-term stability, or impact on the catalytic activity of the main reaction. Flame spray pyrolysis technology, as a continuous and scalable nanomaterial preparation technology, can convert precursor solutions into functional nanoparticles within milliseconds, offering significant advantages such as simple process flow, high production efficiency, and controllable product particle size. Applying this technology to vanadium battery electrode modification holds promise for achieving efficient and controllable deposition of hydrogen evolution suppression clusters.

[0004] Recent research in materials science has shown that the size effect and electronic structure modulation of catalysts can significantly influence their hydrogen adsorption free energy. Sub-nanometer clusters (1 nm to 5 nm) possess unique quantum size effects and surface geometries, which can optimize hydrogen adsorption energy and thus improve hydrogen evolution overpotential. The technical challenge addressed in this invention is how to combine this "cluster size engineering" concept with flame spray pyrolysis technology for the modification of vanadium battery anodes—specifically, depositing hydrogen evolution inhibition clusters of a specific size on a complex three-dimensional carbon felt substrate while maintaining high catalytic activity for vanadium ion reduction. Summary of the Invention

[0005] To address the problems of uncontrollable inhibitor size and impact on the main reaction activity in existing vanadium battery anode hydrogen evolution suppression technologies, this invention provides a vanadium battery electrode modification method based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the anode side. This method uses flame spray pyrolysis technology to deposit sub-nanometer clusters with a size of 1nm~5nm on the anode side of a carbon-based electrode. By utilizing the size effect and electronic structure modulation of the clusters, effective suppression of the hydrogen evolution reaction is achieved, while maintaining the inhibition of hydrogen evolution activity. 3+ / V 2+ The reaction exhibits high catalytic activity.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a vanadium battery electrode with hydrogen evolution suppression clusters deposited on the negative electrode side based on flame spray pyrolysis technology includes the following steps: (1) Pretreatment of carbon-based electrode substrate: The carbon-based electrode substrate is ultrasonically cleaned in acetone, ethanol and deionized water in sequence to remove surface impurities; then it is surface activated in acid solution to introduce oxygen-containing functional groups to enhance the adhesion of subsequent clusters; finally, it is washed with deionized water and dried for later use.

[0007] (2) Preparation of precursor solution: Dissolve at least one hydrogen evolution inhibiting metal precursor in an organic solvent to prepare a dilute precursor solution with a concentration of 0.01 mol / L to 0.1 mol / L. Using a dilute precursor solution helps to form small clusters rather than large particles.

[0008] (3) Flame spray pyrolysis deposition: The dilute precursor solution from step (2) is deposited on the negative electrode side of the pretreated carbon-based electrode substrate using flame spray pyrolysis technology to form a cluster coating. By controlling the process parameters, the clusters are positioned and deposited on the negative electrode side rather than the positive electrode side.

[0009] Cluster size control: By adjusting the precursor solution concentration, deposition time, and flame temperature, sub-nanometer clusters with sizes ranging from 1 nm to 5 nm can be controlled. Clusters of specific sizes possess optimized electronic structures and hydrogen adsorption free energies, which can effectively improve the hydrogen evolution overpotential.

[0010] (4) Post-processing: The obtained electrode is cleaned and dried to obtain a modified electrode with a hydrogen evolution inhibition cluster coating on the negative electrode side.

[0011] Further, in step (1), the carbon-based electrode substrate is a polyacrylonitrile-based carbon felt or carbon paper.

[0012] Further, in step (2), the hydrogen evolution suppressing metal precursor is one or more of the following: nitrates, acetates, and acetylacetone salts of bismuth, lead, cadmium, tin, and zinc; the organic solvent is ethanol, ethylene glycol, 2-ethylhexanoic acid, or a mixture thereof. These metals have high hydrogen evolution overpotentials and are ideal hydrogen evolution suppressing materials.

[0013] Further, in step (3), the parameters for flame spray pyrolysis deposition are: precursor solution feed rate of 1 mL / min to 5 mL / min, preferably 1 mL / min to 3 mL / min; dispersed oxygen flow rate of 5 L / min to 10 L / min, preferably 5 mL / min to 8 mL / min; fuel gas flow rate of 2 L / min to 5 L / min, preferably 2 mL / min to 4 mL / min; and deposition time of 1 min to 10 min, preferably 2 min to 5 min.

[0014] The precursor solution concentration is 0.01 mol / L to 0.1 mol / L, and the size of the clusters is 1 nm to 5 nm; The precursor solution concentration is 0.03 mol / L to 0.06 mol / L, and the size of the cluster is 3 nm to 5 nm; The metal cluster is a single metal cluster, and the metal is selected from one of bismuth, lead, tin, zinc, and cadmium; The alloy cluster is a bimetallic alloy cluster composed of any two of bismuth, lead, tin, zinc, and cadmium, with a molar ratio of (1:10) to (10:1) between the two metals.

[0015] The clusters are metal oxide clusters, obtained by heat-treating the deposited electrode in an oxygen-containing atmosphere at a temperature of 150°C to 300°C.

[0016] Furthermore, the cluster is a single metal cluster, an alloy cluster, or a metal oxide cluster, and a bimetallic alloy structure is formed by introducing a second metal element to further optimize the hydrogen evolution suppression effect.

[0017] This invention provides a modified electrode prepared by the above method, wherein the negative electrode side surface of the electrode has hydrogen evolution inhibition clusters with a size of 1-5 nm and a cluster loading of 0.01 mg / cm³. 2 ~0.5mg / cm 2 .

[0018] This invention provides an application of the modified electrode prepared by the above method, which is particularly suitable for use as a negative electrode in vanadium batteries.

[0019] The design concept of this invention is: This invention creatively combines flame spray pyrolysis technology with cluster science for suppressing hydrogen evolution in vanadium battery anodes, proposing a novel hydrogen evolution suppression strategy based on "cluster size engineering" using flame spray pyrolysis technology. Flame spray pyrolysis technology can complete precursor atomization, decomposition, and particle nucleation growth within milliseconds, providing a technological platform for the efficient and controllable deposition of sub-nanometer clusters. Research shows that the activity of the hydrogen evolution reaction is related to the catalyst's adsorption free energy for hydrogen (ΔG). H Closely related to, the optimal ΔG H It should be close to thermal neutrality (ΔG) H ≈0). When the cluster size decreases to the sub-nanometer scale (1nm~5nm), the quantum size effect and surface coordination unsaturation increase, which can significantly regulate the electronic structure of the cluster, causing a shift in the d-band center position, thereby optimizing the hydrogen adsorption energy and increasing the hydrogen evolution overpotential. Meanwhile, the metals selected in this invention, such as bismuth, lead, cadmium, tin, and zinc, inherently possess high hydrogen evolution overpotentials, and their bulk materials have already exhibited certain hydrogen evolution suppression characteristics. Preparing them into sub-nanometer clusters using flame spray pyrolysis technology further amplifies the performance gains brought about by the size effect. Furthermore, by introducing a second metal to form alloyed clusters, synergistic and ligand effects can be generated, further optimizing the electronic structure and achieving a balance between hydrogen evolution suppression and main reaction catalysis.

[0020] The advantages and beneficial effects of this invention are as follows: 1. The flame spray pyrolysis technology was applied to the hydrogen evolution suppression cluster deposition of vanadium battery negative electrode, realizing the efficient, controllable and continuous preparation of clusters. The process is simple, energy-efficient and easy to scale up.

[0021] 2. The hydrogen evolution suppression strategy based on "cluster size engineering" of flame spray pyrolysis technology can achieve optimized regulation of hydrogen adsorption free energy by precisely controlling the cluster size to 1nm~5nm, and negatively shifting the hydrogen evolution initiation potential by 130mV~240mV.

[0022] 3. By adjusting the precursor concentration and deposition parameters, the cluster size can be controlled within the range of 1nm~5nm or 3nm~5nm, providing customized solutions for different application scenarios.

[0023] 4. The selected metallic material itself possesses a high hydrogen evolution overpotential, and the sub-nano cluster structure further enhances this characteristic. Simultaneously, the small-sized clusters expose more active sites, thus improving the performance of V... 3+ / V 2+ The reaction still maintains good catalytic activity.

[0024] 5. After flame spray pyrolysis deposition, the electrode surface loading material of this invention is in the form of uniformly dispersed clusters, realizing the controllable preparation of sub-nanometer scale clusters on a carbon substrate. Attached Figure Description

[0025] Figure 1 This is a transmission electron microscope image of the Bi cluster modified electrode from Example 1. Detailed Implementation

[0026] The technical solution of the present invention will be described in detail below with reference to the embodiments, but the scope of protection claimed by the present invention is not limited to the embodiments described.

[0027] This invention relates to a method for preparing a vanadium battery modified electrode with hydrogen evolution suppression clusters deposited on the negative electrode side based on flame spray pyrolysis technology, comprising the following steps and process methods: In the specific implementation process, the carbon-based substrate is first cleaned and activated; then a dilute solution containing a hydrogen evolution inhibitor metal precursor is prepared; subsequently, flame spray pyrolysis technology is used to deposit the precursor on the negative electrode side surface; finally, the modified electrode is obtained through post-treatment.

[0028] (1) Substrate pretreatment: The carbon-based electrode substrate was cut into 10cm×10cm pieces and ultrasonically cleaned in acetone, ethanol and deionized water for 30min each. Then, it was immersed in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, it was dried in a vacuum drying oven at 80°C for 12h for later use.

[0029] (2) Preparation of precursor solution: Weigh the hydrogen evolution inhibition metal precursor according to the designed concentration, dissolve it in an organic solvent, and stir magnetically for 2 hours until completely dissolved to obtain a dilute precursor solution with a concentration of 0.01 mol / L to 0.1 mol / L.

[0030] (3) Flame spray pyrolysis deposition: The pretreated carbon-based electrode substrate is fixed on the sample stage of the flame spray pyrolysis device, and the deposition parameters are set to perform flame spray pyrolysis deposition. The dilute precursor solution is deposited on the negative electrode side surface of the pretreated carbon-based electrode substrate to form a cluster coating.

[0031] (4) Post-treatment: After deposition, the electrode is removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material.

[0032] This invention controls sub-nanometer clusters with sizes ranging from 1 nm to 5 nm by adjusting the precursor solution concentration, deposition time, and flame temperature. Clusters of specific sizes possess optimized electronic structures and hydrogen adsorption free energies, effectively increasing the hydrogen evolution overpotential. The precursor solution concentration is 0.01 mol / L to 0.1 mol / L, with cluster sizes ranging from 1 nm to 5 nm; the precursor solution concentration is 0.03 mol / L to 0.06 mol / L, with cluster sizes ranging from 3 nm to 5 nm.

[0033] According to a preferred embodiment of the present invention, the carbon-based electrode substrate is a polyacrylonitrile-based carbon felt or carbon paper.

[0034] According to a preferred embodiment of the present invention, the hydrogen evolution suppressing metal precursor is one or more of bismuth, lead, cadmium, tin, and zinc nitrates, acetates, and acetylacetone salts; the organic solvent is one or more of ethanol, ethylene glycol, and 2-ethylhexanoic acid. These metals have high hydrogen evolution overpotentials and are ideal hydrogen evolution suppressing materials.

[0035] According to a preferred embodiment of the present invention, the parameters for flame spray pyrolysis deposition are as follows: precursor solution feed rate 1 mL / min to 5 mL / min, preferably 1 mL / min to 3 mL / min; dispersed oxygen flow rate 5 L / min to 10 L / min, preferably 5 mL / min to 8 mL / min; fuel gas flow rate 2 L / min to 5 L / min, preferably 2 mL / min to 4 mL / min; and deposition time 1 min to 10 min, preferably 2 min to 5 min.

[0036] According to a preferred embodiment of the present invention, the metal cluster is a single metal cluster, a bimetallic alloy cluster, or a metal oxide cluster. In the bimetallic cluster, the molar ratio of the two metals is (1:10) to (10:1).

[0037] The present invention also provides a modified electrode prepared by the above method, wherein the negative electrode side surface of the electrode has hydrogen evolution inhibition clusters with a size of 1 nm to 5 nm and a cluster loading of 0.01 mg / cm³. 2 ~0.5mg / cm 2 .

[0038] The modified electrode provided by this invention, by precisely controlling the cluster size to 1nm~5nm, can achieve optimized regulation of the hydrogen adsorption free energy. A V0 occurs on the negative electrode side of the modified electrode. 3+ / V 2+ The reduction reaction, with a standard electrode potential of -0.26V vs. SHE, is shifted negatively by 130mV to 240mV, ultimately achieving a standard electrode potential of -0.39V vs. SHE to -0.50V vs. SHE.

[0039] A third aspect of the present invention provides the application of the modified electrode in a vanadium battery, and further, its use as the negative electrode of a vanadium battery.

[0040] The raw materials and equipment used, such as different metal salt precursors and organic solvents, are all commercially available.

[0041] The present invention will now be described in further detail through embodiments.

[0042] Example 1: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0043] (2) Preparation of precursor solution: Weigh bismuth nitrate [Bi(NO3)3·5H2O] and dissolve it in a mixed solvent of ethanol / 2-ethylhexanoic acid (volume ratio 1:1). Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.02mol / L.

[0044] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the surface of the negative electrode side. The process parameters are set as follows: precursor feed rate 2 mL / min, dispersed oxygen flow rate 6 L / min, methane fuel flow rate 3 L / min, and deposition time 3 min.

[0045] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Bi-FSP-1.

[0046] Modified electrode Bi-FSP-1: The Bi cluster size was controlled to be 2nm~3nm by adjusting the precursor concentration (0.02mol / L), feed rate (2mL / min), and deposition time (3min); the cluster loading was approximately 0.08mg / cm³. 2 TEM revealed that the clusters were uniformly dispersed on the carbon fiber surface with a narrow size distribution. Electrochemical tests showed that the hydrogen evolution onset potential shifted negatively to -0.68V vs. SHE. Assembled into a vanadium battery single cell, it achieved a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.8%, and the energy efficiency was 76.1%.

[0047] Figure 1 The image shows the transmission electron microscope (TEM) morphology of the Bi-based deposit on the modified electrode surface obtained in Example 1. As can be seen from the figure, after flame spray pyrolysis deposition, the loaded material on the electrode surface is uniformly dispersed in clusters with a particle size range of 2 nm to 3 nm, confirming that the method can achieve controllable preparation of sub-nanometer-scale clusters on carbon substrates.

[0048] Example 2: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0049] (2) Preparation of precursor solution: Weigh lead nitrate [Pb(NO3)2] and dissolve it in ethanol. Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.03 mol / L.

[0050] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the negative electrode side surface. The process parameters are set as follows: precursor feed rate 3 mL / min, dispersed oxygen flow rate 7 L / min, methane fuel flow rate 4 L / min, and deposition time 2 min.

[0051] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Pb-FSP-2.

[0052] Modified electrode Pb-FSP-2: The Pb cluster size was controlled to be 3nm~4nm by adjusting the precursor concentration (0.03mol / L), feed rate (3mL / min), and deposition time (2min); the cluster loading was approximately 0.06mg / cm³. 2 TEM showed that the clusters were uniformly dispersed on the carbon fiber surface. Electrochemical tests showed that the hydrogen evolution onset potential shifted negatively to -0.65V vs. SHE. Assembled into a vanadium battery single cell, it achieved a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.5%, and the energy efficiency was 75.8%.

[0053] Example 3: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0054] (2) Preparation of precursor solution: Weigh tin acetylacetone [Sn(acac)2] and dissolve it in a mixed solvent of ethanol / 2-ethylhexanoic acid (volume ratio 1:1). Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.01 mol / L.

[0055] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the negative electrode side surface. The process parameters are set as follows: precursor feed rate 1.5 mL / min, dispersed oxygen flow rate 5 L / min, methane fuel flow rate 2.5 L / min, and deposition time 5 min.

[0056] (4) Post-treatment: After deposition, the electrode is removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Sn-FSP-3.

[0057] Modified electrode Sn-FSP-3: The Sn cluster size was controlled to be 1nm~2nm by adjusting the precursor concentration (0.01mol / L), feed rate (1.5mL / min), and deposition time (5min); the cluster loading was approximately 0.04mg / cm³. 2 TEM showed that the clusters were uniformly dispersed on the carbon fiber surface. Electrochemical tests showed that the hydrogen evolution onset potential shifted negatively to -0.62V vs. SHE. Assembled into a vanadium battery single cell, it achieved a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.2%, and the energy efficiency was 75.4%.

[0058] Example 4: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0059] (2) Preparation of precursor solution: Weigh cadmium nitrate [Cd(NO3)2·4H2O] and dissolve it in ethanol. Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.04 mol / L.

[0060] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the negative electrode side surface. The process parameters are set as follows: precursor feed rate 4 mL / min, dispersed oxygen flow rate 8 L / min, methane fuel flow rate 4 L / min, and deposition time 2 min.

[0061] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Cd-FSP-4.

[0062] Modified electrode Cd-FSP-4: The Cd cluster size was controlled to be 4nm~5nm by adjusting the precursor concentration (0.04mol / L), feed rate (4mL / min), and deposition time (2min); the cluster loading was approximately 0.09mg / cm³. 2 TEM showed that the clusters were uniformly dispersed on the carbon fiber surface. Electrochemical tests showed that the hydrogen evolution onset potential shifted negatively to -0.60V vs. SHE. Assembled into a vanadium battery single cell, it achieved a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.8%, and the energy efficiency was 74.9%.

[0063] Example 5: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut carbon paper into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0064] (2) Preparation of precursor solution: Weigh zinc nitrate [Zn(NO3)2·6H2O] and dissolve it in ethanol. Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.02mol / L.

[0065] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the negative electrode side surface. The process parameters are set as follows: precursor feed rate 2.5 mL / min, dispersed oxygen flow rate 6 L / min, methane fuel flow rate 3 L / min, and deposition time 4 min.

[0066] (4) Post-treatment: After deposition, the electrode is removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Zn-FSP-5.

[0067] Modified electrode Zn-FSP-5: The Zn cluster size was controlled to be 2nm~3nm by adjusting the precursor concentration (0.02mol / L), feed rate (2.5mL / min), and deposition time (4min); the cluster loading was approximately 0.07mg / cm³. 2TEM showed that the clusters were uniformly dispersed on the carbon fiber surface. Electrochemical tests showed that the hydrogen evolution onset potential shifted negatively to -0.58V vs. SHE. Assembled into a vanadium battery single cell, it achieved a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.5%, and the energy efficiency was 74.5%.

[0068] Example 6: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut carbon paper into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0069] (2) Preparation of precursor solution: Weigh bismuth nitrate and lead nitrate according to the Bi:Pb molar ratio of 1:1, with a total metal ion concentration of 0.03 mol / L, dissolve them in ethanol, and stir magnetically for 2 hours until completely dissolved to obtain a homogeneous precursor solution.

[0070] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the negative electrode side surface. The process parameters are set as follows: precursor feed rate 2.5 mL / min, dispersed oxygen flow rate 6 L / min, methane fuel flow rate 3 L / min, and deposition time 3 min.

[0071] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material BiPb-FSP-6.

[0072] Modified electrode BiPb-FSP-6: By adjusting the total metal ion concentration to 0.03 mol / L, the feed rate to 2.5 mL / min, and the deposition time to 3 min, the size of the Bi-Pb bimetallic alloy clusters was controlled to be 3 nm to 5 nm; the cluster loading was approximately 0.08 mg / cm³. 2 Due to the synergistic effect of alloying, the hydrogen evolution onset potential shifts negatively to -0.72V vs. SHE. Assembled into a vanadium battery single cell, it achieves a current of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.2%, and the energy efficiency was 81.5%.

[0073] Example 7: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0074] (2) Preparation of precursor solution: Bismuth nitrate and tin acetylacetone were weighed according to the Bi:Sn molar ratio of 2:1, with a total metal ion concentration of 0.03 mol / L. They were dissolved in a mixed solvent of ethanol / 2-ethylhexanoic acid (volume ratio 1:1) and magnetically stirred for 2 hours until completely dissolved to obtain a homogeneous precursor solution.

[0075] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the negative electrode side surface. The process parameters are set as follows: precursor feed rate 2 mL / min, dispersed oxygen flow rate 5 L / min, methane fuel flow rate 2.5 L / min, and deposition time 4 min.

[0076] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material BiSn-FSP-7.

[0077] Modified electrode BiSn-FSP-7: By adjusting the total metal ion concentration to 0.03 mol / L, the feed rate to 2 mL / min, and the deposition time to 4 min, the size of the Bi-Sn bimetallic alloy clusters was controlled to be 2 nm to 3 nm; the cluster loading was approximately 0.06 mg / cm³. 2 The alloying synergistic effect shifts the hydrogen evolution initiation potential negatively to -0.70V vs. SHE. When assembled into a vanadium battery single cell, it achieves a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.9%, and the energy efficiency was 76.3%.

[0078] Example 8: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0079] (2) Preparation of precursor solution: Weigh bismuth nitrate [Bi(NO3)3·5H2O] and dissolve it in a mixed solvent of ethanol / 2-ethylhexanoic acid (volume ratio 1:1). Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.015 mol / L.

[0080] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the surface of the negative electrode side. The process parameters are set as follows: precursor feed rate 5 mL / min, dispersed oxygen flow rate 6 L / min, methane fuel flow rate 3 L / min, and deposition time 1 min.

[0081] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Bi-FSP-8 (low concentration).

[0082] Modified electrode Bi-FSP-8 (low concentration): By adjusting the precursor concentration to 0.015 mol / L, the feed rate to 5 mL / min, and the deposition time to 1 min, the Bi cluster size was controlled to be 2 nm~3 nm; the cluster loading was approximately 0.06 mg / cm³. 2 TEM showed that the clusters were uniformly dispersed on the carbon fiber surface. Electrochemical tests showed that the hydrogen evolution onset potential shifted negatively to -0.69V vs. SHE. Assembled into a vanadium battery single cell, it achieved a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.4%, and the energy efficiency was 79.7%.

[0083] Example 9: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0084] (2) Preparation of precursor solution: Weigh lead nitrate [Pb(NO3)2] and dissolve it in ethanol. Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.04 mol / L.

[0085] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the surface of the negative electrode side. The process parameters are set as follows: precursor feed rate 3.5 mL / min, dispersed oxygen flow rate 7 L / min, methane fuel flow rate 4 L / min, and deposition time 3 min.

[0086] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Pb-FSP-9 (medium concentration).

[0087] Modified electrode Pb-FSP-9 (medium concentration): The Pb cluster size was controlled to be 3nm~4nm by adjusting the precursor concentration to 0.04mol / L, the feed rate to 3.5mL / min, and the deposition time to 3min; the cluster loading was approximately 0.08mg / cm³. 2 TEM showed that the clusters were uniformly dispersed on the carbon fiber surface. Electrochemical tests showed that the hydrogen evolution onset potential shifted negatively to -0.64V vs. SHE. Assembled into a vanadium battery single cell, it achieved a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.2%, and the energy efficiency was 79.5%.

[0088] Example 10: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0089] (2) Preparation of precursor solution: Weigh bismuth nitrate [Bi(NO3)3·5H2O] and dissolve it in a mixed solvent of ethanol / 2-ethylhexanoic acid (volume ratio 1:1). Stir magnetically for 2 hours until completely dissolved to prepare an ultra-dilute precursor solution with a concentration of 0.08 mol / L.

[0090] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the negative electrode side surface. The process parameters are set as follows: precursor feed rate 1 mL / min, dispersed oxygen flow rate 5 L / min, methane fuel flow rate 2 L / min, and deposition time 2 min.

[0091] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Bi-ultrasmall-10 (ultra-low concentration).

[0092] Modified electrode Bi-ultrasmall-10 (ultra-low concentration): By adjusting the precursor concentration to 0.08 mol / L, the feed rate to 1 mL / min, and the deposition time to 2 min, the Bi cluster size was controlled to be 1 nm~1.5 nm; the cluster loading was approximately 0.3 mg / cm³. 2 Due to the more pronounced quantum effects at ultra-small sizes, the hydrogen evolution onset potential shifts negatively to -0.71V vs. SHE. Assembled into a vanadium battery single cell, it achieves a current of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.3%, and the energy efficiency was 76.4%.

[0093] Example 11: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0094] (2) Preparation of precursor solution: Weigh bismuth nitrate [Bi(NO3)3·5H2O] and dissolve it in a mixed solvent of ethanol / 2-ethylhexanoic acid (volume ratio 1:1). Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.02mol / L.

[0095] (3) Flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the surface of the negative electrode side. The process parameters are set as follows: precursor feed rate 2 mL / min, dispersed oxygen flow rate 6 L / min, methane fuel flow rate 3 L / min, and deposition time 3 min.

[0096] (4) Heat treatment: After natural cooling, the electrode is taken out and placed in an oxygen-containing atmosphere. It is subjected to oxidation heat treatment at 300℃ for 2 hours to obtain the modified electrode material BiOx-11.

[0097] Modified electrode BiOx-11: Through oxidation treatment, the Bi oxide cluster size is 2nm~4nm; the cluster loading is approximately 0.08mg / cm³. 2 The hydrogen evolution initiation potential shifts negatively to -0.67V vs. SHE. Assembled into a vanadium battery single cell, at 300mA / cm²...2 Tested at current density, the coulombic efficiency reached 98.8%, and the energy efficiency was 76.0%.

[0098] Example 12: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0099] (2) Preparation of precursor solution: Weigh bismuth nitrate [Bi(NO3)3·5H2O] and dissolve it in a mixed solvent of ethanol / 2-ethylhexanoic acid (volume ratio 1:1). Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.02mol / L.

[0100] (3) Low-temperature flame spray pyrolysis deposition: The pretreated carbon felt was fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side was covered with a mask, exposing only the negative electrode side surface. The process parameters were set as follows: precursor feed rate 2 mL / min, dispersed oxygen flow rate 6 L / min, methane fuel flow rate 2 L / min (reducing the fuel flow rate to lower the flame temperature), and deposition time 3 min. A water-cooled sample stage was used to maintain the substrate temperature at approximately 50°C.

[0101] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material Bi-lowtemp-12.

[0102] Modified electrode Bi-lowtemp-12: Low-temperature deposition reduces the cluster nucleation rate, improves dispersion, and narrows the size distribution (2nm~3nm, standard deviation <0.3nm); cluster loading is approximately 0.01mg / cm³. 2 Excellent dispersibility shifts the hydrogen evolution initiation potential negatively to -0.70V vs. SHE. When assembled into a vanadium battery single cell, it achieves a performance of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 99.1%, and the energy efficiency was 84.3%.

[0103] Example 13: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0104] (2) Preparation of precursor solution: Weigh zinc nitrate and dissolve it in a mixed solvent of ethanol / ethylene glycol (volume ratio 1:1). Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.1 mol / L.

[0105] (3) Low-temperature flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the surface of the negative electrode side. The process parameters are set as follows: precursor feed rate 5 mL / min, dispersed oxygen flow rate 10 L / min, methane fuel flow rate 5 L / min, and deposition time 1 min.

[0106] (4) Post-treatment: After deposition, the electrode was removed and dried in a vacuum drying oven at 60°C for 12 hours to obtain the modified electrode material BiSn-FSP-13.

[0107] Modified electrode BiSn-FSP-13: The Bi-Sn cluster size was controlled to be 2nm~3nm by adjusting the precursor concentration (0.1mol / L), feed rate (5mL / min), and deposition time (1min); the cluster loading was approximately 0.45mg / cm³. 2 The hydrogen evolution initiation potential shifts negatively to -0.52V vs. SHE. Assembled into a vanadium battery single cell, at 300mA / cm²... 2 Tested at current density, the coulombic efficiency reached 98.3%, and the energy efficiency was 82.4%.

[0108] Example 14: In this embodiment, a method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side is as follows: (1) Substrate pretreatment: Cut the carbon felt into 10cm×10cm pieces and clean it by ultrasonication for 30min each in acetone, ethanol and deionized water. Then, soak it in 5wt% HNO3 solution at 60°C for 2h for surface activation. After rinsing repeatedly with deionized water until neutral, dry it in a vacuum drying oven at 80°C for 12h for later use.

[0109] (2) Preparation of precursor solution: Weigh bismuth nitrate [Bi(NO3)3·5H2O] and dissolve it in ethylene glycol solvent. Stir magnetically for 2 hours until completely dissolved to prepare a dilute precursor solution with a concentration of 0.1 mol / L.

[0110] (3) Low-temperature flame spray pyrolysis deposition: The pretreated carbon felt is fixed on the sample stage of the flame spray pyrolysis device, and the positive electrode side is covered with a mask, exposing only the surface of the negative electrode side. The process parameters are set as follows: precursor feed rate 1 mL / min, dispersed oxygen flow rate 10 L / min, methane fuel flow rate 5 L / min, and deposition time 10 min.

[0111] (4) Heat treatment: After deposition, the electrode is removed and placed in an oxygen-containing atmosphere for 2 hours of oxidation heat treatment at 150°C to obtain the modified electrode material BiOx-14.

[0112] Modified electrode BiOx-14: The BiOx cluster size was controlled to be 2nm~4nm by adjusting the precursor concentration (0.1mol / L), feed rate (1mL / min), and deposition time (10min); the cluster loading was approximately 0.5mg / cm³. 2 Clusters were uniformly dispersed on the carbon fiber surface. Electrochemical tests showed that the hydrogen evolution initiation potential shifted negatively to -0.77V vs. SHE. The modified electrode was used as the negative electrode to assemble a vanadium battery single cell, achieving a voltage of 300 mA / cm². 2 Tested at current density, the coulombic efficiency reached 98.5%, and the energy efficiency was 76.4%.

[0113] The results of the examples demonstrate that the flame spray pyrolysis technology of this invention can successfully construct hydrogen evolution suppression clusters of specific sizes on the negative electrode side of a carbon-based electrode through a simple and controllable deposition process. By adjusting the precursor concentration, the cluster size can be precisely controlled within the sub-nanometer range of 1 nm to 5 nm. Adjusting the deposition time and flame temperature can further optimize the cluster size distribution. Introducing a second metal to form alloyed clusters produces a synergistic effect that enhances the hydrogen evolution suppression effect. Low-temperature deposition improves cluster dispersion, achieving multi-dimensional and precise control of the microstructure on the negative electrode side. The prepared modified electrode, with its sub-nanometer clusters exhibiting optimized electronic structure and hydrogen adsorption free energy due to size effects, significantly enhances the suppression ability against hydrogen evolution side reactions, shifting the hydrogen evolution initiation potential negatively by 130 mV to 240 mV while maintaining the inhibition of Vo. 3+ / V 2+ The electrode exhibits high catalytic activity for the reaction. Through its inherent cluster size engineering design and negative electrode side deposition strategy, this electrode effectively coordinates the multiple requirements of vanadium battery negative electrodes for high hydrogen evolution overpotential, high catalytic activity, and stable cycle life, achieving a coulombic efficiency of over 98%. It provides a key electrode material solution for developing next-generation high-performance, high-stability vanadium batteries.

Claims

1. A method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology to deposit hydrogen evolution suppression clusters on the negative electrode side, characterized in that, Includes the following steps: (1) Pretreatment of carbon-based electrode substrate: The carbon-based electrode substrate is ultrasonically cleaned to remove surface impurities, then surface activated in acid solution, and finally washed with deionized water and dried for later use. (2) Preparation of precursor solution: Dissolve at least one hydrogen evolution inhibiting metal precursor in an organic solvent to prepare a precursor solution with a concentration of 0.01 mol / L to 0.1 mol / L; (3) Flame spray pyrolysis deposition: The precursor solution is deposited on the negative electrode side surface of the pretreated carbon-based electrode substrate using flame spray pyrolysis technology to form a coating with a cluster size of 1nm~5nm, thus obtaining the electrode; (4) The electrode is post-processed or heat-treated to obtain a vanadium battery modified electrode with hydrogen evolution suppression clusters deposited on the negative electrode side.

2. The method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology for depositing hydrogen evolution suppression clusters on the negative electrode side, as described in claim 1, is characterized in that... In step (3), the parameters for flame spray pyrolysis deposition are: precursor solution feed rate of 1 mL / min to 5 mL / min, dispersed oxygen flow rate of 5 L / min to 10 L / min, fuel gas flow rate of 2 L / min to 5 L / min, and deposition time of 1 min to 10 min.

3. The method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology for depositing hydrogen evolution suppression clusters on the negative electrode side, as described in claim 2, is characterized in that... The parameters for flame spray pyrolysis deposition are as follows: precursor solution feed rate of 1 mL / min to 3 mL / min, dispersed oxygen flow rate of 5 L / min to 8 L / min, fuel gas flow rate of 2 L / min to 4 L / min, and deposition time of 2 min to 5 min.

4. The method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology for depositing hydrogen evolution suppression clusters on the negative electrode side, as described in claim 2, is characterized in that... In step (1), the carbon-based electrode substrate is a polyacrylonitrile-based carbon felt or carbon paper; In step (2), the hydrogen evolution inhibitor metal precursor is one or more of the following: nitrates, acetates, and acetylacetone salts of bismuth, lead, cadmium, tin, and zinc; and the organic solvent is one or a mixture of ethanol, ethylene glycol, and 2-ethylhexanoic acid.

5. A method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology for depositing hydrogen evolution suppression clusters on the negative electrode side, as described in claim 2 or 4, characterized in that... The clusters in the modified electrode surface coating are single metal clusters, alloy clusters, or metal oxide clusters.

6. The method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology for depositing hydrogen evolution suppression clusters on the negative electrode side, as described in claim 5, is characterized in that... In the single metal cluster, the metal is selected from one of bismuth, lead, tin, zinc, and cadmium; The alloy cluster is a bimetallic alloy cluster composed of any two metals selected from bismuth, lead, tin, zinc, and cadmium, with a molar ratio of (1:10) to (10:1) between the two metals.

7. A method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology for depositing hydrogen evolution suppression clusters on the negative electrode side, as described in claim 2 or 4, characterized in that... The post-processing process is as follows: the electrode is cleaned and dried to obtain a modified electrode with a hydrogen evolution inhibition cluster coating on the negative electrode side; The heat treatment process is as follows: the electrode is heat-treated in an oxygen-containing atmosphere at a temperature of 150℃~300℃ to obtain a modified electrode with a hydrogen evolution inhibition cluster coating on the negative electrode side.

8. A method for preparing a vanadium battery modified electrode based on flame spray pyrolysis technology for depositing hydrogen evolution suppression clusters on the negative electrode side, as described in claim 2 or 4, characterized in that... The precursor solution concentration is 0.03 mol / L to 0.06 mol / L, and the size of the cluster is 3 nm to 5 nm.

9. A vanadium battery modified electrode for suppressing hydrogen evolution clusters deposited on the negative electrode side, prepared by the method described in claim 2 or 4, characterized in that, The modified electrode surface has a cluster loading of 0.01 mg / cm³. 2 ~0.5mg / cm 2 The standard electrode potential is -0.39V vs. SHE ~ -0.50V vs. SHE.

10. The application of a vanadium battery modified electrode with hydrogen evolution suppression clusters deposited on the negative electrode side in a vanadium battery, wherein the electrode is prepared by the method described in claim 2 or 4, characterized in that... The modified electrode is the negative electrode of a vanadium battery.